The Effect of Entrepreneurial Orientation and Organisational Culture on Firm Performance: The Mediating Role of Innovation - Waris Ali Khan; Ramraini Ali Hassan; Muhammad Zulqarnain Arsha; Muhammad Ali Arshad; Umair Kashif; Umair Kashif; Syed Azizi Wafa Syed Khalid Wafa (2020)
This study is concerned with conceptual model development, which examines the innovation influence on the relationship of organisational culture, entrepreneurial orientation and performance of large manufacturing firms in Pakistan. A total of 399 questionnaires were distributed to large manufacturing firms in Pakistan to assess the relationships between organisational culture, entrepreneurial orientation, innovation, and firm performance. The findings reveal that entrepreneurial orientation significantly influences the performance of large manufacturing firms in Pakistan. Meanwhile, the results also indicated that other factors such as organisational culture do not significantly relate to the manufacturing firm’s performance. Interestingly, the results had shown that the factor of innovation significantly mediated the relationships between organisational culture, entrepreneurial orientation and firm performance. Based on the results, it can be summarised that the mechanism used to enhance the innovative culture in the organisation will also contribute to the introduction, adoption and diffusion of innovations. Additionally, these factors would contribute to increased performance and achievement in the near future. Indeed, this statement is supported by numerous current and past studies conducted in Pakistan, where scholars found that innovation is the primary impetus of firm performance. However, there exists a very limited number of studies regarding the impact of innovation on organisational culture and entrepreneurial orientation in manufacturing firms in Pakistan. This study would lead to a significant contribution to the prevailing literature by empirically examining the relationship between organisational culture, entrepreneurial orientation, innovation and firm performance.